The Validity of Okun’s Law: An Empirical Evidence for Nigeria - Obodoechi, Divine Ndubuisi; Onuoha, Charles Uchenna (American International Journal of Social Science Research, 2019)
This paper empirically investigates the relationship between economic growth and unemployment in Nigeria under the Okun’s Law framework. The Auto Regressive Distributed Lag model approach, the ARDL Bounds Test and Cointegration Test were employed in this paper. Economic Growth was also regressed on unemployment, log of industrial output, log of net foreign assets, log of foreign direct investment and population growth so as to know the impact of these variables on output. The research findings indicated that high the Okun’s specification does not hold in the Nigeria, the impact of economic growth on unemployment is negative and insignificant. We did however find that there is a positive impact of unemployment on economic growth, meaning that the phenomena of jobless growth may be in play in the economy. The Johansen Co-integration test failed to establish evidence of long run relationship between GDP, industrial output, unemployment, foreign direct investment net foreign assets and population growth. The ECM could not be employed because the variables were integrated of different orders. It was however found there exist a significant positive relationship between the aforementioned variables and GDP except for population growth. The government should consider the Industrial Sector as a priority sector in a bid for better economic growth and development. Population control measures should also be put in play to ensure that the population does not exceed the economic carrying capacity. The government should also play an important role in abating unemployment in the economy using direct and indirect schemes and strategies.